Heterotopia and Heterochrony - Fabriano Fabbri (ZoneModa Journal, 2022)
The essay investigates certain aspects of contemporary fashion through the “Tenet effect”, that is, researching the dynamics of style that are based on the reinterpretation and rewriting of elements of the past, as well as on their updating. The title of the contribution recalls the work of one of the French “nouveaux philosophes”, Michel Foucault, while the “Tenet effect” derives from cinema, precisely from Tenet by Cristopher Nolan, released in 2020. The reference figure of the interpretation proposed in the essay it is that of Riccardo Tisci, in his long phase of collaboration at Givenchy’s; at the helm of the famous French fashion house, the designer puts into practice his techniques of estrangement and reworking of history and the museum, at the same time proving his extraordinary abilities in the genetic tampering of the expressive codes of fashion. The contribution analyzes the men’s and women’s collections in which Tisci has been able to demonstrate that he is a worthy representative of the quotationism typical of his generation of born “around 1970”, in parallel with the visions of Alexander McQueen or Nicolas Ghesquière.